POTENSI PENGEMBANGAN PENDAPATAN ASLI DAERAH (Studi di Kabupaten Lombok Timur) - H. SYAHRUDIN (Universitas Mahasaraswati Mataram, 2018)
The aim of the research is to identify various potential sources of regional real income which develop and formulate strategy of regional real income. Student interview, documentation, and focus group discussion are used for collecting data. Data analyzed using collection ratio, regional real income proportion, regional real income growth, and SWOT analysis. The research result showed that 3 from 4 sources of own regional income which are potential to be developed, namely regional tax, regional retribution and profit of regional asset management. The development strategy for 3 potential own regional income include optimizing regional tax, regional retribution as well as profit of regional asset management, and business plan of district governmental enterprise